2018
DOI: 10.1016/j.marchem.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Zinc association with surface-bound iron-hydroxides on cultured marine diatoms: A zinc stable isotope perspective

Abstract: Uptake of trace metals by marine phytoplankton for metabolic use exerts a fundamental control on their marine geochemical distributions. Moreover, such trace metals limit primary productivity over large areas of the surface ocean. As such, an understanding of the mechanisms and extent of phytoplankton uptake are essential components of oceanic trace metal chemistry. Efforts to quantify intra-cellular quotas of phytoplankton are complicated by the presence of metals adsorbed to external surfaces, including surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Dissolved δ 66 Zn observed in this study also possess isotopically light signature in the surface water (Figures and a). In addition to the seminal culture study (John et al, ), a recent culture study also indicated that Zn adsorption onto the surface‐bound Fe‐hydroxides may cause bulk δ 66 Zn to be isotopically heavy (Köbberich & Vance, ). Scavenging seems to be a major process causing the surface isotopically light Zn signature in the oceans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dissolved δ 66 Zn observed in this study also possess isotopically light signature in the surface water (Figures and a). In addition to the seminal culture study (John et al, ), a recent culture study also indicated that Zn adsorption onto the surface‐bound Fe‐hydroxides may cause bulk δ 66 Zn to be isotopically heavy (Köbberich & Vance, ). Scavenging seems to be a major process causing the surface isotopically light Zn signature in the oceans.…”
Section: Discussionmentioning
confidence: 99%
“…The low dissolved δ 66 Zn observations are apparently at odds with the expectation that isotopically light Zn would be preferentially taken up by phytoplankton, leaving behind heavy Zn in dissolved pool. Actually, culture experiments have observed that phytoplankton take up isotopically light Zn relative to the culture medium, with 0.2 to 0.4‰ difference between phytoplankton and the medium (John et al, ; Köbberich & Vance, , ; Samanta et al, ). However, recent studies have argued that Zn fractionation of biological uptake can be insignificant due to the complexation effect of organic ligands in culture medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…J o u r n a l P r e -p r o o f change in the coordination environment of dissolved and of adsorbed Zn could, however, be responsible for the isotopic fractionation based on the findings of other studies (Aucour et al, 2015;Aucour et al, 2017;Guinoiseau et al, 2016;Juillot et al, 2008;Köbberich and Vance, 2018;Little et al, 2014;Pokrovsky et al, 2005). Indeed, Aucour and co-workers studied the biogeochemical cycle of Zn isotopes at an infiltration basin receiving urban stormwater, in which Phalaris arundinacea (reed canary grass) developed spontaneously, and identified tetrahedral Zn species sorbed on iron oxides (Aucour et al, 2015).…”
Section: Possible Mechanisms Driving the Isotope Fractionationmentioning
confidence: 95%
“…Of the two groups of organisms cultured here for Zn isotopes, the data for cyanobacteria are the 246 most novel. Previous studies have presented data for diatoms Köbberich and 247 Vance, 2017;Köbberich and Vance, 2018), while Samanta et al (2017) have published Zn 248 isotope data for another eukaryote group, the coccoliths. Thus, we first discuss the variation 249 within the cyanobacteria strains cultured, before moving on to compare these new data with the 250 new and published data for eukaryotes.…”
mentioning
confidence: 99%